Packing 1-plane Hamiltonian cycles in complete geometric graphs - Trao, Hazim Michman; Ali, Niran Abbas; Chia, Gek L.; Kilicman, Adem (Faculty of Sciences and Mathematics, University of Nis, 2019)
Counting the number of Hamiltonian cycles that are contained in a geometric graph is #P-complete even if the graph is known to be planar [15]. A relaxation for problems in plane geometric graphs is to allow the geometric graphs to be 1-plane, that is, each of its edges is crossed at most once. We consider the following question: For any set P of n points in the plane, how many 1-plane Hamiltonian cycles can be packed into a complete geometric graph Kn? We investigate the problem by taking two different situations of P, namely, when P is in convex position, wheel configurations position. For points in general position we prove the lower bound of k − 1 where n = 2k + h and 0 ≤ h < 2k. In all of the situations, we investigate the constructions of the graphs obtained.